The role of the media in strengthening freedom of expression and democratic institutions in Uzbekistan - Nurullayevich, Eshbekov Bakhodir (Journal of Multidisciplinary Academic Business Studies, 2025)
Purpose: This study examines the role of mass media in strengthening freedom of expression and supporting the development of democratic institutions in Uzbekistan. It emphasizes how the media operates not only as an information provider but also as a strategic tool that facilitates communication between the state and society, creating a transparent and open information environment essential for democracy. Research methodology: This study uses historical-logical, content, and systematic analyses, along with observation, to examine the evolution of media functions, legislative frameworks ensuring media freedom, and institutional practices affecting press independence and accountability in Uzbekistan. Results: The findings indicate that mass media play a decisive role in shaping public awareness, political participation, and civic culture. The transition into the digital age has expanded the functions of the media, making it a central driver of social and political change. This study underscores the urgency of building strong institutional, legal, and economic mechanisms to preserve independence, limit manipulation, and promote balanced regulation between freedom of speech and digital security, especially against misinformation and harmful content. Conclusions: Mass media in Uzbekistan has become a cornerstone for advancing democratic values and civic engagement. Sustaining this role requires coherent state policies that encourage openness and mitigate digital threats. Limitations: This study is limited to the national context of Uzbekistan and focuses primarily on institutional and legislative dimensions, thus not capturing informal or regional media dynamics. Contribution: This research enriches the scholarly debate on transitional democracies by providing insights and recommendations for policymakers, media institutions, and academics to foster free expression and consolidate democratic governance.